ยุทธศาสตร์ความร่วมมือทางเศรษฐกิจอิรวดี-เจ้าพระยา-แม่โขง: กรณีศึกษาไทย - กัมพูชา - ปิยพัชร เหล่าสมบัติ (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
This independent study aimed to examine the efficiency of Ayeyawady-Chao Phraya-Mekong Economic Cooperation Strategy (ACMECS) between Thailand and Cambodia through the implementation of various projects under the ACMECS framework that have been ongoing and are likely to have an effect on the relationship between the two countries. Due to the fact that Thailand and Cambodia have maintained a longtime relationship along their shared borders, consequently, the histories, cultures, religions, and ways of life of the people of both countries are similar. As a result, Thai and Cambodian people embrace powerful ties in terms of trade, investment, and tourism. Furthermore, Thailand and Cambodia have a cooperation framework or strategies in place to strengthen economic relations. The author utilized the Ayeyawady-Chao Phraya-Mekong Economic Cooperation Strategy (ACMECS) as a case study in this independent investigation. Under the leadership of Prime Minister Thaksin Shinawatra, Thailand was the pioneer in establishing ACMECS. After era-specific changes in government and prime ministerial leadership persisted until the administration of General Prayut Chan-o-cha, the foreign policy objectives of Thailand experienced a change during this period. Therefore, the author was intrigued to investigate a variety of Thailand-Cambodia projects under the ACMECS framework. This helped to find out which projects are presently ongoing and are anticipated to impact the international relationship between Thailand and Cambodia. The author conducted an extensive review and analysis of related documents, reports, theses, news, and academic articles in order to collect and analyze all the obtained data. According to the findings of the study, both Cambodia and Thailand have given prominence to the ACMECS framework, which consists of continuing implementations of concrete projects that have accomplished their objectives.